2015
DOI: 10.21608/jappmu.2015.52769
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Early Heat Stress on the Productive Performance and Physiological Response in Some Local Chicken Strains

Abstract: This experiment was conducted to study the effect of heat stress at early age on heat shock proteins, plasma Triiodothyronine (T3), thermal reaction, productive performance, egg quality, and immune response of Matrouh and Inshas chicks. Seven hundred and twenty, one day old chicks (360 Matrouh chicks and 360 Inshas chicks) were used in this study. Birds from each strain were divided into three groups. The first was not treate and kebt as acontrol group (T1), the birds in the second group were exposed to (42°C-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…These results agreed with those of Abuoghaba (2017), who found a significant decrease in Hubbard broilers body weight gain under thermal manipulations compared with the control group. Also, the findings of Galal et al, (2015) showed a significant decrease body weight gain for Matrouh chicks exposed to thermal group (42-43°C) after hatch as compared with those of the control group (37.5°C) as well as the 2 th week of age. In contrast, Joseph et al, (2006) found that the body weight gain in Ross broiler chicks exposed to 36.6°C during early incubation phase significantly decreased as compared with that of the control group.…”
Section: Body Weight Gainmentioning
confidence: 87%
“…These results agreed with those of Abuoghaba (2017), who found a significant decrease in Hubbard broilers body weight gain under thermal manipulations compared with the control group. Also, the findings of Galal et al, (2015) showed a significant decrease body weight gain for Matrouh chicks exposed to thermal group (42-43°C) after hatch as compared with those of the control group (37.5°C) as well as the 2 th week of age. In contrast, Joseph et al, (2006) found that the body weight gain in Ross broiler chicks exposed to 36.6°C during early incubation phase significantly decreased as compared with that of the control group.…”
Section: Body Weight Gainmentioning
confidence: 87%